Attempting and achieving weight loss and maintenance - Rasquilha, Inês Chaparro Roque dos Santos Telo (2017)
This dissertation thought to provide a comprehensive understanding of weight loss- and maintenance-related processes among adults. Specifically, it comprises a set of five studies that were designed to i) determine the prevalence of weight control attempts and identify correlates, personal strategies, and motives underlying these attempts; ii) examine behavioral and psychological characteristics as predictors of successful weight loss and maintenance; and iii) examine psychological predictors of physical activity, a critical behavior for successful weight control. Studies I and II reflect the state of the art regarding the prevalence of weight control attempts among adults on a global and national level, respectively, showing that weight is a matter of concern to a significant portion of the adult population. Study III aimed for a more in-depth understanding of who succeeds in weight loss and maintenance, showing that there is a multiplicity of potentially successful behaviors and strategies. Subsequently, study IV showed that psychological factors underlying the weight control behaviors, such as positive body image and autonomous motivation, have a critical role in the process. Finally, study V confirmed that more autonomous forms of motivation are key for maintaining physical activity behavior over time in those trying to achieve weight loss and maintenance. The findings in this thesis highlight the need for, and importance of developing long-term individualized approaches for successful weight loss and maintenance, under the umbrella of motivation and related psychological factors. Future weight management initiatives would benefit from targeting combinations of evidence-based weight control strategies and the improvement of body image and motivation quality as potential precursors of those strategies, in order to promote long-term weight loss maintenance. Furthermore, it has become clear that weight control attempts are prevalent in Portugal and worldwide and consequently changes and trends should be monitored regularly in order to inform and advance future practice.